A complex of Transversotrematidae (Platyhelminthes: Digenea) associated with mullid fishes of the Indo-West Pacific Region, including the descriptions of four new species of Transversotrema - Hunter, Janet A.; Hall, Kathryn A.; Cribb, Thomas H. (Zootaxa, 2012)
Phylogenetic analysis based on ribosomal DNA markers indicates that there is a discrete clade of species of Transverso-trema Witenberg, 1944 associated with mullid fishes of the Indo-West Pacific, although there is only one previous recordof transversotrematids from these fishes. Each of the species in this clade bears broad morphological similarity to previousconcepts of either Transversotrema haasi Witenberg, 1944 or Transversotrema licinum Manter, 1970, yet none of them isattributed here to either of these species. Four new species of Transversotrema are described from mullid fishes of thetropical and sub-tropical Indo-West Pacific using a combination of morphology, morphometric analysis and DNA se-quencing. Transversotrema cabrarum n. sp. is described from Parupeneus spilurus (Bleeker) from Ningaloo Reef (Aus-tralia), and recorded from Parupeneus cyclostomus (Lacepède), Parupeneus pleurostigma (Bennett) and Parupeneustrifasciatus (Lacepède) from the same location. Transversotrema chevrarum n. sp. is described from Lizard Island (GreatBarrier Reef, Australia) from Parupeneus ciliatus (Lacepède), and further recorded from Parupeneus barberinus(Lacepède), P. cyclostomus, Parupeneus indicus (Shaw), Parupeneus multifasciatus (Quoy & Gaimard) and P. trifasciatusat the same location. Transversotrema cutmorei n. sp. is described from Upeneus tragula Richardson from Moreton Bay,Australia. Transversotrema tragorum n. sp. is described from Parupeneus indicus from Lizard Island and recorded fromP. barberinus, P. ciliatus P. cyclostomus, P. multifasciatus and P. trifasciatus from the same location. An additional spe-cies, also from mullids from Lizard Island, is delineated on the basis of molecular data, but not formally described. Like many other transversotrematids, the species described here appear to have limited geographical distributions.